The Role of Product Quality, Brand Image and Consumer Trust in Purchasing Decisions at Pocong Pancong Pleburan Semarang - Risnaldi Rahadian; Masitha Fahmi Wardhani (Jurnal Indonesia Sosial Sains, 2025)
The culinary industry in Indonesia continues to grow, including in the city of Semarang, which faces intense competition between business actors. Understanding the factors that influence consumer purchasing decisions is important for the sustainability of the culinary business. This study aims to analyze the effect of product quality, brand image, and consumer confidence on purchasing decisions at Pocong Pancong Pleburan Semarang. This study uses a quantitative method with an exploratory approach. Respondents in this study were consumers who had made purchases at Pocong Pancong, which were selected using purposive sampling method. Data were collected through a questionnaire that had been tested for validity and reliability. Data analysis was carried out using multiple linear regression with partial, simultaneous, and coefficient of determination tests through statistical software. The results showed that product quality, brand image, and consumer confidence have a significant effect on purchasing decisions, both individually and as a whole. Of the three factors, consumer confidence has the most dominant influence on purchasing decisions, followed by product quality and brand image. The coefficient of determination shows that the three variables explain most of the variation in purchasing decisions, while other factors still need further research.